Grit on Students Who Did Not Reach The Target of Memorizing The Qur'an at Ma’had Ta’limul Qur'an (Mataqu) Junior High School Utsman Bin Affan - Hanifa, Shabrina; Muna, Zurratul; Hafnidar, Hafnidar (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This research explores the concept of grit among students who failed to reach their Qur’an memorization targets, a topic that has received limited attention in educational psychology and Islamic learning contexts. The study aims to clarify the aspects of grit and the factors that influence its development among students at SMP MATAQU Utsman Bin Affan. Using a qualitative phenomenological approach, five participants, three female and two male, third-grade junior high school students were selected through purposive sampling. The data were collected through interviews, observations, and documentation, and analyzed using Interpretative Phenomenological Analysis. The findings show that three participants demonstrated grit characterized by passion and perseverance, while two participants had not yet developed consistent persistence in achieving long-term goals. Internal factors such as interest, disciplined practice, goal orientation, and hope were identified as key components of shaping grit, whereas external factors, including parental involvement, structured school programs, and supportive learning and memorizing culture, further strengthened students’ determination. The results indicate that grit in Qur’an memorization is influenced not only by personal motivation but also by social and institutional support, suggesting that teachers and parents play an important role in cultivating students’ persistence and commitment.